Chemical profiling, quantitation, and bioactivities of Du-Zhong tea. (15th November 2022) - Shi, Xiqing; Luo, Shengbo; Zhong, Kan; Hu, Xinghua; Zhang, Zijia
Highlights: 52 Compounds were identified from tender and mature EUL using UPLC-Q-TOF MS. HPLC-DAD method was used to determine the contents of nine compounds in EUL. The contents of nine compounds in tender EUL were higher than mature EUL. C and d -grade Du-Zhong tea exhibited higher bioactivities. Abstract: Du-Zhong tea is a health beverage produced from Eucommia ulmoides leaves (EUL) as raw materials using traditional tea processing and Chinese herbal pieces processing methods. To evaluate the differences between tender leaves and mature leaves of Du-Zhong tea, UPLC-Q-TOF MS was used to analyze the constituents in EUL collected in April and August. A total of 52 compounds, including iridoids, phenylpropanoids, flavonoids, lignans, and other types of compounds were identified. The contents of nine ingredients in the tender and mature leaves of E. ulmoides were determined by HPLC-DAD analysis. The results show that the average contents of the compounds in tender leaves were significantly higher than those in mature leaves. Lastly, the antioxidant and antipancreatic lipase activities of commercial Du-Zhong tea made by leaves of different maturity were evaluated. Du-Zhong tea with d -grade exhibited relatively higher antioxidant, while C-grade exhibited greater lipase inhibitory activities.